2009
DOI: 10.1051/0004-6361/200811309
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of an eruptive flare loop system

Abstract: Context. Flares, eruptive prominences and coronal mass ejections are phenomena where magnetic reconnection plays an important role. However, the location and the rate of the reconnection, as well as the mechanisms of particle interaction with ambient and chromospheric plasma are still unclear. Aims. In order to contribute to the comprehension of the above mentioned processes we studied the evolution of the eruptive flare loop system in an active region where a flare, a prominence eruption and a CME occurred on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…The corresponding velocity inferred from the drift rate is comparable to the group-based displacement velocity of the zero-drift stripes in groups IV and V (see Fig. 6(d) and Table 2), and it lies in the range of velocity obtained from studies of the other events (Khan et al 2006(Khan et al , 2007Romano et al 2009;Yan et al 2013). We note that the upward motion of the source in stripe 9 cannot come from an anti-sunward moving plasma blob, because such a blob could not penetrate the newly reconnected field lines carried downward by the reconnection outflow.…”
Section: (B)) Based Onsupporting
confidence: 71%
“…The corresponding velocity inferred from the drift rate is comparable to the group-based displacement velocity of the zero-drift stripes in groups IV and V (see Fig. 6(d) and Table 2), and it lies in the range of velocity obtained from studies of the other events (Khan et al 2006(Khan et al , 2007Romano et al 2009;Yan et al 2013). We note that the upward motion of the source in stripe 9 cannot come from an anti-sunward moving plasma blob, because such a blob could not penetrate the newly reconnected field lines carried downward by the reconnection outflow.…”
Section: (B)) Based Onsupporting
confidence: 71%
“…By far the favorite loop event for radio studies during the RHESSI period is SOL2002-08-24T01:12 (X3.1) on the west limb (Karlický 2004;Li & Gan 2005;Melnikov 2006;Tzatzakis et al 2008;Romano et al 2009;Reznikova et al 2009;, which also produced a fast (1900 km s −1 ) CME and an energetic particle event at the Earth. Figure 5.1 shows images in HXRs, microwaves and the EUV 195Å band (Fe XII and Fe XXIV) during the early part of the impulsive phase, for which RHESSI data are available.…”
Section: "Loop" Flaresmentioning
confidence: 99%
“…Gamma ray emission detected by SONG began at 00:58 UT, near the time of the O VI peak, and continued for 9 minutes (Kuznetsov et al 2006). Romano et al (2009) studied the evolution of this flare. They found that the prominence became unstable at 00:52 UT, the same time that the RHESSI hard X-rays began to brighten.…”
Section: Appendixmentioning
confidence: 99%